The unattainable fruit: a symbolic analysis of male infertility - Parducci Arruda, Camila; Alencar Lima, Maria Thereza (O Mundo da Saúde, 2012)
According to the World Health Organization’s estimates, one in every ten couples in the world population is infertile1. Current research shows the impact of the diagnosis to be greater for the couple when infertility affects men. This qualitative research followed the referential system of analytical psychology, aiming to understand symbolically masculine infertility. For doing this, a meeting was carried out with a couple involved in a psycho-diagnostic process for assisted fecundation in which they were asked to construct a Time line for allowing the extension of the analysis and a broader understanding of the process experienced in life. We also asked the male subject some expressive productions (tree drawing, thematic drawing and free drawing), subsequently analyzed using the technique of symbolic amplification based on authors such as Furth2 and Van Kolck3. As regards maleness, it was possible to observe the conflict between being a modern man (to be a sensitive, welcoming and affectionate man) and an archaic one (to be a man of power and success). Infertility signified as emptiness and hole translates the force of an ideal to be reached, a role of hegemonic man, being biological paternity understood as a safe haven for this possibility of self-realization. It translates also all virtualities, potentialities of that which would fill out or would pass through his opening. It is connected to expectations, newness, strangeness, the sudden revelation of a presence, that of fertility.